Turnover-based corporate income taxation and corporate risk-taking - Fernando Siahaan; Harald Amberger; Caren Sureth (Arbeitskreis Quantitative Steuerlehre (arqus), 2023)
This study investigates the effect of a Turnover-based Corporate Income Tax (TbCIT) on corporate risk-taking. TbCIT is a simplified presumptive tax levied on a firm's turnover and commonly applied to SMEs and hard-to-tax income. Using a rich sample of Indonesian firms for the years 2009 to 2021, we provide evidence that corporate risk-taking is negatively associated with a firm's TbCIT exposure. The negative effect is stronger for firms in industries with high profit margins and firms with prior year losses. However, we find no association between risk-taking and the effective TbCIT rate. Overall, our findings extend prior research on the effects of limited risk sharing between taxpayers and the government by showing that turnover-based taxation can depress corporate risk-taking. Our study also informs policymakers about potential unintended consequences of adopting simplified, turnover-based tax regimes.
Keywords: H25; H32; G32; O53; 330; turnover-based tax; corporate income tax; risk-taking; SMEs taxation